Analysis of physical and chemical transformations during thermal spraying of coatings based on carbides of tungsten and chromium. Issue 1 (November 2020) - Kharlamov, Yu O; Sokolov, V I; Krol, O S; Romanchenko, O V
Abstract: The formation of structure and properties of thermal coatings is largely determined by the transformation intensity of sprayed materials at all stages of obtaining of coating. It is shown that during D – gun spraying, in order to ensure optimal conditions for leading transformations and phenomena that have a decisive influence on structure and properties of sprayed coatings, composition of combustible mixture, geometry and dimensions of barrel, conditions for introducing powder into the barrel and a unit dose of powder, spraying distance, timing of spraying cycle and other technological methods can be used. The possibility of transformation in powders of tungsten carbide and chromium under different methods of thermal spraying is analyzed and the structure and properties of coatings are obtained. The influence of the conditions of D – gun spraying on spraying distances, gas flow rates, type of powder, etc.; phase composition and properties of coatings is studied. The basic physicochemical transformations that accompany D – gun spraying of coatings of alloy WC – C, such as oxidation and reduction of tungsten carbide in high – temperature oxygen – containing media, interaction of composite coating components are considered problems of modelling of bonding of particles with a part surface during thermal spraying of coatings are considered.